Mass violence and the self from the French wars of religion to the Paris Commune - Brown, Howard G. (Ithaca London Cornell University Press, 2018)
"Examines the visual and textual media depicting personal suffering caused by incidents of mass violence in France from 1560 to 1880 that helped to provoke repeated collective traumas, which in turn forged new social identities and fostered the psychological processes of the modern self"--
Literaturverzeichnis: Seite 229-276
Auch als Online-Ausgabe erschienen
First published 2018 by Cornell University Press
Keywords: Violence -- History -- France; Political Violence -- History -- France; Psychic trauma -- History -- France; Collective Memory -- History -- France; Identity (Psychology) -- History -- France; Group Identity -- History -- France; Self (Philosophy) -- History -- France